Toxicity Assessment of Cyanobacterial Strains Using Brine Shrimp and Mouse Bioassay - Majit, Jasmina; Mohamad, Samsur; Hassan, Ruhana (2010)
Cyanobacterial samples were collected from aquaculture ponds in Sarawak and Sabah. Strain belonging to Microcystis sp. were isolated and maintained in laboratory cultures. Mass cultures were performed and the cells were harvested in their late exponential phase of growth. Each strain was lypholized and extracted using methanol to get the crude extract. Five different concentrations were tested in brine shrimp assay and the extracts were toxic with a LC50 of less than 50 μg/ml within 24 hrs observation. Mouse bioassay was done via intraperitoneal injection of 1.0 ml of a lysate of toxin extract into ±20 g white mice. The preliminary screening of toxin extracts using brine shrimp and mouse bioassay indicates that the strains are potentially toxin producer species and subjected to further examine using high performance liquid chromatography method.